Polymerization of Phenylacetylene-Based Monodendrons with Alkoxy Peripheral Groups and Oxygen/Nitrogen Permeation Behavior of Their Membranes - Takashi Kaneko; Kazuaki Sato; Yoshihiko Uchiya; Masahiro Teraguchi; Toshiki Aoki (International Journal of Polymer Science)
Monodendron monomers with alkoxy peripheral groups were synthesized, and the focal point of monodendrons, terminal acetylene, was polymerized with rhodium catalyst to yield corresponding polydendrons with a high molecular weight. The polydendrons were soluble in common organic solvents and readily formed membranes. Oxygen permselectivity was improved in the polydendrons with a space-persistent dendritic crowd. It was found that the well-defined dendritic and rod-like structure of the polydendrons was useful for permselective membrane.